Ionospheric And Geomagnetic Disturbance Study During Seismic Activity In Southeast Asia Using Space Borne And Ground Sensor - Rizal, Nur Awatiff Mohamad (2021)
Many studies on the pre-earthquake involving various methods have been conducted to understand the earthquake activity. The Lithosphere-Atmosphere- Ionosphere Coupling (LAIC) effect describes what physical processes are involved prior to an earthquake. Southeast Asia is a region where earthquakes have a high frequency to occur, and the earthquake’s studies in this region still lack and poorly understood. Therefore, this study aims to understand the pre-earthquake behaviour by investigating the behaviour of the geomagnetic field and the components before an earthquake. The geomagnetic field data is collected using space borne sensors and ground sensors. Satellite data will be collected by the CHAMP and Swarm satellites, while MAGDAS will collect ground sensor data. This study is based on the major earthquakes (M>6.5) that happened in Southeast Asia for eleven years, from 2008 to 2018. Two weeks prior to every listed earthquake, the data was collected, filtered, and distinguished from any unrelated geomagnetic anomalies such as solar activities and magnetic storms. Based on the result, at least one disturbed profile would appear before a major earthquake. The dominant component that showed the most significant anomalies on every disturbed profile was the y-component and N-component for satellites and MAGDAS data, respectively. Lastly, the mass collecting data from both satellite and ground sensors hopefully will be helpful to the improvement for the future real-time earthquake precursor in the Southeast Asia region.